2017
DOI: 10.1037/rep0000140
|View full text |Cite
|
Sign up to set email alerts
|

Cognition among community-dwelling individuals with spinal cord injury.

Abstract: Purpose/Objective To compare the cognitive profiles of a well-characterized sample of adults with and without spinal cord injury (SCI) using the NIH Toolbox – Cognition Battery (NIHTB-CB). Research Method/Design 156 community-dwelling individuals with SCI were recruited from three academic medical centers. 156 individuals without SCI were selected from the NIHTB-CB normative database. The main outcome measures were the demographically-adjusted NIHTB-CB subtest and composite scores. Results Individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Not only in animal models but also in human cognitive impairment after SCI has been reported in recent years. A US study of SCI patients in residential communities showed that after SCI, the risk of cognitive impairment is increased, mainly impairing patients' processing speed and executive function for specific tasks [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only in animal models but also in human cognitive impairment after SCI has been reported in recent years. A US study of SCI patients in residential communities showed that after SCI, the risk of cognitive impairment is increased, mainly impairing patients' processing speed and executive function for specific tasks [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a concerted effort has been made to assess the NIH-Toolbox (including the flanker task) for use in clinical populations . Construct validity for the flanker task has been shown for traumatic brain injury , spinal cord injury (M. L. Cohen et al, 2017), and stroke patients (Carlozzi et al, 2017). Finally, base rate information (Holdnack et al, 2017) and test interpretation analyses (Nitsch et al, 2017) have been performed.…”
Section: Methodsmentioning
confidence: 99%
“…The NIHTB-CB has many advantages as it is: (1) applicable across the lifespan, (2) brief, (3) non-proprietary, (4) based on state-of-the-art test theories and technology, and (5) available in both English and Spanish versions (Mungas et al, 2014). The validity and utility of the battery has been shown in cognitively unimpaired adults (Heaton et al, 2014;Mungas et al, 2014;Weintraub et al, 2013), and clinical samples with spinal cord injury Cohen et al, 2017), traumatic brain injury (TBI; Nitsch et al, 2017;, stroke Carlozzi, Tulsky, et al, 2017;Nitsch et al, 2017;, and intellectual disabilities (Hessl et al, 2016). In addition, a study including adults with varied cognitive statuses provided supportive findings for the validity of NIHTB-CB in assessing neurocognitive domains related to dementia (Hackett et al, 2018).…”
Section: Introductionmentioning
confidence: 99%